Flow characteristics over coral reef - Ow, Wei Chen. (2009)
Experiments done on porous mats that represent artificial coral reefs showed that wave set-up induced by wave breaking have a higher maximum set-up occurring when the smooth plane is in place representing a smothered reef-top. Different parameters such as water depth, wave height and frequency were used during the experiment to determine the response of the resulting wave set-up and the effects they have on wave breaking. Breaking in shallow water seems to be primarily dependent on water depth as shown by the equation ≈ 0.78 b b d H [CERC, 1984] which is widely adopted by current coastal practices. When wave breaks, part of the wave energy will create a pressure gradient across the reef-top known as wave set-up [Hearn, 1999, Lugo-Fernandez et al, 1998]. The resulting wave set-up induced appears to have an influence on wave breaking as wave set-up adds to the existing level of water depth. The increase in water depth was shown to decrease wave set-up while increased wave height was shown to increase the level of wave set-up. Frequency, on the other hand, which is indirectly proportional to wave period, was observed to decrease wave set-up with increment. This means that increasing the wave period will increase the level of wave set-up. However, Gourlay (1996) observed that there is an upper limit after which the wave period will no longer increase wave setup. Different configurations of coral reefs were also seemed to have an effect of the wave set-up. However, the experiment conducted was modeling a fringing reef that is often found closer to the coastline. The porosity of the mat was established in a separate experiment. The value of the porosity will not be used in this report as only a single type of porous mat was used and the lacking a range of variability to determine the effects it could have on wave set-up. Generally, coral reefs seem to reduce the amount of energy carried by the waves through wave breaking and bottom friction. The resulting impact affects wave set-up. However, this report only investigates the level of wave set-up induced with the different parameters in place. More research will need to be done to better determine the effectiveness of coral reefs as waves continue to propagate towards the shore even after it breaks.